2017
DOI: 10.21873/anticanres.11387
|View full text |Cite
|
Sign up to set email alerts
|

Different Gene Expression and Activity Pattern of Antioxidant Enzymes in Bladder Cancer

Abstract: The aim of this study was to evaluate the possible role in and contribution of antioxidant enzymes to bladder cancer (BC) etiology and recurrence after transurethral resection (TUR). We enrolled 40 patients with BC who underwent TUR and 100 sex- and age-matched healthy controls. The analysis was performed at diagnosis and recurrence, taking into account the time of recurrence. Gene expression of catalase (CAT), glutathione peroxidase 1 (GPX1) and manganese superoxide dismutase (SOD2) was determined in peripher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 26 publications
2
17
0
Order By: Relevance
“…Such ROS accumulation induces cellular damage that may promote cancer development as well as its metabolic phenotype [ 13 - 15 , 27 ]. In fact, most of the studies about SOD2 expression and cancer have shown that overexpression of this enzyme is associated with the presence of metastases and poor prognosis in many malignancies, such as lymphomas [ 28 , 29 ], glioblastoma [ 30 ], bladder [ 31 ], lung [ 32 ], colorectal [ 33 ], breast [ 34 ], penile [ 35 ], gastric [ 36 ], esophageal [ 37 ] and oral cancer [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Such ROS accumulation induces cellular damage that may promote cancer development as well as its metabolic phenotype [ 13 - 15 , 27 ]. In fact, most of the studies about SOD2 expression and cancer have shown that overexpression of this enzyme is associated with the presence of metastases and poor prognosis in many malignancies, such as lymphomas [ 28 , 29 ], glioblastoma [ 30 ], bladder [ 31 ], lung [ 32 ], colorectal [ 33 ], breast [ 34 ], penile [ 35 ], gastric [ 36 ], esophageal [ 37 ] and oral cancer [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…In general, radiation promotes GSH synthesis [90]. Because rapamycin and everolimus can affect GSH synthesis, the use of mTOR inhibitors might increase the effectiveness of radiotherapy [91,92]. In addition to antioxidant enzymes, the NRF2-dependent xCT system could promote the radioresistance of solid tumors.…”
Section: Mtor-dependent Antioxidant Mechanism In Solidmentioning
confidence: 99%
“…In addition, interactions between GPX3 and the p53-inducible gene 3 (PIG3) protein leads to activation of the apoptosis in prostate cancer cells (34). A retrospective study based on 40 BC patients reported that high GPX3 expression level in plasma might be predictive indicator for BC diagnosis and recurrence after transurethral resection (35). However, based on 405 BC samples, our results demonstrated that higher GPX3 expression level may predict an early UICC stage and better prognosis.…”
Section: Discussionmentioning
confidence: 66%